International Security, The United Nations And The Post-Cold War Era - McCoubrey, H.; Morris, J.C. (Journal of Malaysian and Comparative Law, 1999)
The end of the Cold War in the 1980s signalled a major change in the global security environment which had existed for most of the first half century of the UN era. This variation in the modern pattern of international relations has necessitated a radical review of international defence and security architecture, although it would be erroneous to represent this as having been in any way a clean break from past experience. It is rather the case that long-standing problems in international relations have presented themsevles in changed forms and in so doing have demanded new, and possibly more effective, responses.